Effects of Heat Input on Morphology of Thin‐Wall Components Fabricated by Wire and Arc Additive Manufacturing. Issue 4 (14th January 2021) - Jiang, Fengchun; Sun, Laibo; Huang, Ruisheng; Jiang, Hui; Bai, Guangyong; Qi, Xiaopeng; Liu, Chuanming; Su, Yan; Guo, Chunhuan; Wang, Jiandong
Abstract : In the process of wire and arc additive manufacturing (WAAM), it is crucial to improve the surface quality and maintain a uniform building morphology. Unacceptable morphology of components influences the surface roughness and deposition efficiency, limiting the application of WAAM in the fabrication of complex‐shaped components. Herein, linear energy density is used to estimate the applied heat input. The single‐pass single‐layer bead morphology is analyzed to establish the relationship between linear energy density and the bead width ratio to bead height. In addition, four four‐layer components under different heat inputs are deposited to reveal the process of multilayer deposition. According to the morphology and surface appearance, heat input effects on surface roughness, straightness, and deposition efficiency are investigated. Then, a relationship is established to predict the outcomes of heat input on deposition quality. It is inferred that good deposition performance can be obtained when the linear energy density lies around 600 J mm −1 . A simulation based on the Simufact welding software is made on temperature field distribution and thermal cycles to illustrate the relationship, confirmed by 3D scanning results. At last, based on the investigations, a uniform and well‐formed thin‐wall component is fabricated, and its deposition efficiency can reach 80%. Abstract : A model is established to illustrate the geometry evolution of single‐layer deposition when applying various heat inputs. Some assessment parameters are defined to evaluate the deposition quality and morphology of multilayer fabrications under different heat inputs. Based on the analysis of heat input effects on the geometry, the deposition efficiency of a 25‐layer fabrication can reach 80%.